PENGEMBANGAN E-MODUL MENGGUNAKAN APLIKASI CANVA PADA TEMA SELALU BERHEMAT ENERGI SUBTEMA MANFAAT ENERGI - Elgiana Sukma Hermara; Mira Mirawati; Tatang Muhajang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
E-module is an electronic module that was developed by utilizing the availability of 21st century technology as an effort to improve learning outcomes in accordance with predetermined learning objectives. This research aims to determine the feasibility of using e-modules using the Canva application in the learning process of students on the theme of always saving energy, sub-theme energy benefits. This research uses a Research and Development (R&D) approach, with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The results of research on e-module development using the Canva application on the theme of always saving energy, sub-theme energy benefits were declared "Very Feasible". The validation test results from the experts were obtained as follows, Indonesian language material experts 80%, science material experts 88%, media experts 90%, and language experts 84%, so that the validation test results obtained an average percentage of 86%. Apart from that, the results obtained from limited trials carried out on students were with an average percentage of 88.3% because it was able to overcome boring learning by providing more active and fun learning for students.